2022
DOI: 10.1061/(asce)ee.1943-7870.0001982
|View full text |Cite
|
Sign up to set email alerts
|

Turn up the Dial: System Dynamics Modeling of Resource Allocations toward Rural Water Supply Maintenance in East Africa

Abstract: Water stress is increasingly affecting hundreds of millions of people around the world. In East Africa, severe and persistent drought periods negatively impact health and livelihoods. Drought increases reliance on mechanized boreholes to extract groundwater. However, without adequate resource allocations, effective monitoring of borehole functionality, and reliable maintenance service, breakdown rates increase and downtimes last many months. Our study applies system dynamics modeling to investigate the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Ultimately, the challenge may be more political and institutional than financial in achieving coordination and compliance to longterm local goals over short-term project objectives, as previous research has demonstrated the potential value of reprioritizing funding allocations from the installation of new schemes toward maintenance provision. 3 The application of system dynamics modeling as a collaborative analysis tool provided a platform for emergent understanding of complex system behavior and may be particularly valuable for investigating the effects of sustainability interventions. The interviewees who informed model parameters experienced greater understanding of the complexity of rural water service delivery in Kitui over time, 29 as did the researchers who co-developed the model.…”
Section: ■ Resource Requirements For Scale-upmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultimately, the challenge may be more political and institutional than financial in achieving coordination and compliance to longterm local goals over short-term project objectives, as previous research has demonstrated the potential value of reprioritizing funding allocations from the installation of new schemes toward maintenance provision. 3 The application of system dynamics modeling as a collaborative analysis tool provided a platform for emergent understanding of complex system behavior and may be particularly valuable for investigating the effects of sustainability interventions. The interviewees who informed model parameters experienced greater understanding of the complexity of rural water service delivery in Kitui over time, 29 as did the researchers who co-developed the model.…”
Section: ■ Resource Requirements For Scale-upmentioning
confidence: 99%
“…It is likely that stronger coordination with donor and NGO projects would close the funding gap. Ultimately, the challenge may be more political and institutional than financial in achieving coordination and compliance to long-term local goals over short-term project objectives, as previous research has demonstrated the potential value of reprioritizing funding allocations from the installation of new schemes toward maintenance provision …”
Section: Resource Requirements For Scale-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the world, water is a precious, essential and, regrettably, scarce resource (Dritsas & Trigka, 2023), and in recent years, water crisis and water scarcity have become important problems (Rahim et al, 2020); also climate change has added to this crisis (Libey et al, 2022) and has intensified drought in many parts of the world (Smith & Wang, 2008). One of the harmful consequences of drought is the reduction of the quantity and quality of water resources (Akbari et al, 2022; Babaei et al, 2013), which has a direct impact on the lives of all humans in all parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…the Bayesian method has a complete theoretical basis and easy-to-understand mathematical properties, the prior and conditional probability are difficult to obtain in practical applications. Therefore, the method has great limitations [4].…”
mentioning
confidence: 99%